Analisis dan Perancangan Sistem Informasi Pemesanan Customized Jersey pada Injers Malang Berbasis Web - Jajang Ogi Wisono; Djoko Pramono; Mochammad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Injers (Indonesia Jersey) Malang is a garment / clothing business UKM built by PT. Askes (Persero) East Java Regional VII, which is engaged in Malang local sports equipment apparel. But the problem in terms of ordering goods is still often experienced, namely the process carried out still manually makes the production party must wait for the data manually too. The growing age has an impact on the increasingly tight business competition using technology, this has triggered the Malang Injers to build a system of ordering goods information in order to suppress the problems experienced. To build an information system there is a concept that is made for the basis of system development, namely Software Development Life Cycle (SDLC). One SDLC framework is Use Case Driven Object Modeling with UML or commonly called ICONIX process. ICONIX process consists of 6 processes, namely requirements, analysts / preliminary designs, preliminary design reviews, detailed design, critical design review and implementation. This study explains how to build the system needed by Malang Injers at the stage of analyzing needs and designing the system using ICONIX process until the evaluation stage. The evaluation used is consistency analysis and correctness. In the consistency analysis test results in the percentage of RCI (Requirement Consistency Index) of 100%, while the correctness test produces a category of â€œcorrectnessâ€.